A Simple High-Performance Liquid Chromatography for Determining Lapatinib and Erlotinib in Human Plasma. Issue 6 (December 2016) - Ohgami, Masahiro; Homma, Masato; Suzuki, Yoshiharu; Naito, Kanako; Yamada, Motoko; Mitsuhashi, Shoichi; Fujisawa, Fumie; Kojima, Hiroshi; Kaburagi, Takayuki; Uchiumi, Keiko; Yamada, Yutaka; Bando, Hiroko; et al.
Abstract : Background: Lapatinib and erlotinib are used for cancer treatment, showing large interindividual variability. Therapeutic drug monitoring may be useful for assessing the clinical outcomes and adverse events. A simple high-performance liquid chromatography UV method was developed for the determination of lapatinib and erlotinib in human plasma. Methods: An aliquot of plasma sample spiked with internal standard was treated with acetonitrile to precipitate the proteins. Lapatinib and erlotinib were separated on an octadecylsilyl silica gel column using a mobile phase consisting of acetonitrile, methanol, water, and trifluoroacetic acid (26:26:48:0.1) pumped at a flow rate of 1.0 mL/min. The detection wavelength was set at 316 nm. Results: The calibration curves for lapatinib and erlotinib were linear (r = 0.9999) in the range of 0.125–8.00 mcg/mL. The extraction recoveries for both lapatinib and erlotinib at the plasma concentration of 0.125–8.00 mcg/mL were higher than 89.9% with coefficients of variation less than 3.5%. The coefficients of variation for intraday and interday assays of lapatinib and erlotinib were less than 5.1% and 6.1%, respectively. Conclusions: The present method can be used for blood concentration monitoring for lapatinib or erlotinib in exactly the same conditions.